Multicomponent Determination of Pesticides in Mineral Water by Gas Chromatography-Mass Spectrometry - Baspinar, Meral; Demir, Cevdet (Asian Journal of Chemistry, 2010)
Analytical procedures were developed for the identification and quantification of pesticides in natural and fruit flavoured mineral waters. The concentrations of pesticides in mineral waters are expected to be at below the ng/L level, which requires preconcentration of analytes and improved detection limits. Solid phase extraction and liquid-liquid extraction procedures were developed for preconcentration and detection was performed with large-volume injection gas chromatography-mass spectrometry by means of a programmable temperature vapourizer. The selectivity of the detection procedure was increased by using selective ion monitoring mode. Validation parameters such as linearity, linear range, accuracy, detection and quantification limits were evaluated. The mean percentage recoveries of pesticides by liquid-liquid extraction ranged from 72 ± 1 (aldrin) to 101 ± 3 % (4,4-DDT). The values using solid phase extraction procedure varied between 74 ± 1 (atrazine) and 102 ± 3 % (a endosulfan). The limits of detection for the pesticides ranged from 15 to 100 ng/L. The concentrations of pesticides ranged from 71 to 530 ng/L in samples extracted with solid phase extraction and from 66 to 1092 ng/L in samples extracted with liquid-liquid extraction procedure. Malathion was only determined in cherry aroma 1 at concentration of 385 ± 1 ng/L. Aldrin was only determined in cherry aroma 1, chlorpyrifos in mineral water 1 and bromopropylate in apple aroma at concentrations of 1092 ± 103 ng/L, 423 ± 7 ng/L and 638 ± 5 ng/L after liquid-liquid extraction.